Boosting students’ creativity in the EFL class through higher order thinking activities - Pokhrel, Vidhya (Journal of NELTA, 2018)
This article is a depiction of my concern in the implementation of higher order thinking activities in the EFL classroom. The article has explored the idea of higher order thinking along with its impact on students. Most importantly, it has given the scenario of how competent the teachers have to be in order to plan the lessons with higher order thinking activities. The article has picked up the real classroom scenarios where students came up with better output with higher order thinking activities. The content, the process and the product were all made the major concern in the article. Overall, the article develops an awareness on the exercise of higher order thinking activities in the EFL classroom.